The Effusion of Grace within the Sharīʿa Loop:: A (Re-)Consideration of Sufi-ulamaic Institutional Charisma in Ottoman Sunnism (c.16th–20th Centuries) - Pantić, Nikola (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This paper examines how Ottoman early modern Sufi-ʿulamāʾ conceptualized the charisma of their office, based on the prophetic charismatic image, and transmitted through sainthood (wilāya). It focuses on baraka and discusses what made it divine in ulamaic theology, analyzing how it was monopolized by Ottoman religious institutions, to serve as a theological charisma-building tool. Discussing the interdependence of institutional and individual charisma within the Ottoman religious office, this article tests Max Weber’s theories of charisma on studies of Sunni Muslim religious institutions in the post-prophetic period, specifically during early modernity.